Circular Business Model: Development of Reusable Camera to Reduce E-Waste from Disposable Camera - Sasongko, Agung; Sari, Emelia; Rubiyanto, Raihan Cecarrio; Akbari, Annisa Dewi; Sunaryo, Thalia; Rinanti, Astri; Mamat, Tengku Nur Azila Binti Raja (Fakultas Teknik, Universitas Pasundan, 2026)
An increase demand for reusable cameras among the millennial and Z-generation in Indonesia has created a significant environmental dilemma, considering the consequently increasing production of electronic waste. Although the principle of circular economy has been adapted in various electronic industry sector, its implementation in particularly the camera industry is still left to explore. This study aims to design and validate a comprehensive circular business model for reusable cameras in Indonesia that can measurably reduce electronic waste from disposable cameras while maintaining economic and environmental value creation To achieve this objective, the study applies a circular business model canvas integrated with a qualitative case study on reusable camera usage in Indonesia, a systematic literature review on circular economy practices in the electronics sector, and a product sustainability assessment using quantitative metrics. This paper concludes that the proposed circular business model for reusable cameras represents the most suitable development option because it simultaneously reduces e‑waste from disposable cameras and enhances economic and environmental value creation in Indonesia. This study also develops three hybrid business model strategies – ‘ownership plus, ‘try-before-you-buy’, and ‘community-based ownership pools’ – all of which accommodate consumer ownership preferences in Indonesia while maintaining the circular economy principles. This paper concludes by highlighting the operability of the circular business model for camera and its potential contribution to the sustainable development goals. This notwithstanding, its implementation requires multi-stakeholder collaboration, investments in digital infrastructure, capacity building, and government support on regulations.